Cyclodextrin‐Templated Porphyrin Nanorings1. Issue 30 (10th June 2014) - Liu, Pengpeng; Neuhaus, Patrik; Kondratuk, Dmitry V.; Balaban, T. Silviu; Anderson, Harry L.
Abstract α‐ and β‐Cyclodextrins have been used as scaffolds for the synthesis of six‐ and seven‐legged templates by functionalizing every primary CH2OH with a 4‐pyridyl moiety. Although these templates are flexible, they are very effective for directing the synthesis of macrocyclic porphyrin oligomers consisting of six or seven porphyrin units. The transfer of chirality from the cyclodextrin templates to their nanoring hosts is evident from NMR and circular dichroism spectroscopy. Surprisingly, the mean effective molarity for binding the flexible α‐cyclodextrin‐based template within the six‐porphyrin nanoring (74 M) is almost as high as for the previously studied rigid hexadentate template (180 M). The discovery that flexible templates are effective in this system, and the availability of a template with a prime number of binding sites, open up many possibilities for the template‐directed synthesis of larger macrocycles.